2011
DOI: 10.1590/s2179-975x2011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eutrophication and Typha domingensis Pers on methanogenesis in tropical constructed wetland

Abstract: AIM: Constructed wetlands (CWs) have shown to be an efficient way for removing nutrients from wastewaters. However, a negative effect is the emission of greenhouse gases (GHGs). Methane (CH4) is a GHG released from the organic matter degradation under anaerobic conditions by methanogenic bacteria. In CWs, the excessive nutrient inputs may stimulate both primary production and methanogenesis and then affect the overall cost-benefit balance of this system. Here, we assessed the role of cattail stands (Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
0
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
2
0
0
2
Order By: Relevance
“…In addition, methane production also can be linked to labile carbon via root exudates [36] [37], which can increase the consumption of oxygen and production of substrates for methanogenesis. These results corroborate those of other studies that also revealed high methane concentrations in sediment colonized by emergent macrophytes [34] [38]- [40]. However, the presence of emergent macrophytes can also inhibit methanogenesis via the oxidation of sediment.…”
Section: Resultssupporting
confidence: 92%
“…In addition, methane production also can be linked to labile carbon via root exudates [36] [37], which can increase the consumption of oxygen and production of substrates for methanogenesis. These results corroborate those of other studies that also revealed high methane concentrations in sediment colonized by emergent macrophytes [34] [38]- [40]. However, the presence of emergent macrophytes can also inhibit methanogenesis via the oxidation of sediment.…”
Section: Resultssupporting
confidence: 92%
“…However, the greatest PMP rate of a freshwater lagoon (Cabiúnas) in our study was only 3.36 nmol g -1 day -1 . In an earlier study in our study and others (Chan et al, 2002;Bastviken et al, 2010;Neves et al, 2011). Almost all of the lagoons showed much higher sediment CH 4 concentrations in the littoral region than in the limnetic region.…”
Section: 22differences Between the Limnetic And Littoral Region (supporting
confidence: 67%
“…Assim, para compreender o papel das macrófitas aquáticas para dado reservatório são importantes estudos de avaliação da variação de biomassa (BIUDES; CAMARGO, 2006;POMPÊO et al, 2001;BOTTINO et al, 2013;TRINDADE et al, 2011;GONÇALVES et al, 2011), composição química (HENRY-SILVA;CAMARGO, 2006a;BARBIERI;ESTEVES, 1991;HENRY-SILVA et al, 2001;HENRY, 2010;; produtividade primária (PIEDADE et al, 1991;PENHA et al, 1999;SANTOS;, área de colonização (POMPÊO; MOSCHINI-CARLOS, 1995BATISTA et al, 2013), crescimento (HENARES;CAMARGO, 2014;POMPÊO et al, 1999a), decomposição (SANTINO;BIANCHINI Jr, 2015;FONSECA et al, 2013;SILVA et al, 2011), mas não se pode esquecer estudos mais abrangentes, por exemplo, sobre o meio físico (VALE et al, 2014;ALBERTONI et al, 2014;ALVES DA SILVA et al, 2014;DINIZ et al, 2005;PEREIRA et al, 2012) ou mesmo de cunho mais fisiológico com as macrófitas aquáticas (BIZZO et al, 2014;GRIPP et al, 2013;SUZUKI, 2013;CREMA et al, 2011;GOMES et al, 2011), ou mesmo de outras abordagens não tão regulares, principalmente nos estudos ocorridos no Brasil (BINI et al, 2005;FERNANDES et al, 2013;PINTO et al, 2013;CARNIATTO et al, 2012;TRAVAINI-LIMA;NEVES et al, 2011).…”
Section: Abordagens Nos Estudosunclassified
“…Devido à importância desse elemento para o metabolismo dos ecossistemas e como fator explicativo do processo de eutrofização e da biomassa de clorofila a presente, por exemplo, poderá não haver interesse em removê-lo da planilha de trabalho apenas por ter alguns poucos dados com valores abaixo do LD. Para que isso não ocorra, como critério para validação desses dados e a manutenção das concentrações de FID na planilha de trabalho, para os campos correspondentes às estações de coletas ou as profundidades onde as concentrações do FID não foram possíveis de quantificar, os técnicos poderão avaliar a pertinência de anotar metade do valor do LD, como sugerido por Newman et al (1989), Lewis et al (2007) e Department of Energy & Environment (2012). Alternativa possível é alterar o método de laboratório, com procedimentos analíticos mais sensíveis do que os empregados.…”
Section: Testes Preliminares E Trabalhos De Campo E Laboratóriounclassified